Covid-19 Di Indonesia: Pemodelan Dan Analisis Perbedaan Kondisi Perekonomian Sebelum Dan Sesudah Pandemi - Muhammad Rismawan Ridha (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2021)
The Covid-19 pandemic has disrupted various human economic activities. Restrictions on people's movements with Large-Scale Social Restrictions (PSBB) have resulted in sluggish production activities and capital outflows which have resulted in a weakening of the rupiah exchange rate. In addition to impacting the exchange rate, the Covid-19 pandemic also had an impact on declining sales in the automotive sector. This study aims to model the increase in the number of positive cases of Covid-19 in Indonesia as well as to identify differences in economic conditions before and after the pandemic and the enactment of the PSBB. The data source used from the website of the Covid-19 Handling Task Force, Bank Indonesia, and the Indonesia Stock Exchange. Based on the results of the analysis, the ARIMA (2,1,1) ARCH (1) model is the right model to be used to predict positive case data for Covid-19. In addition, paired sample t-test analysis shows that there are significant differences in economic conditions in Indonesia before and after the Covid-19 pandemic and the implementation of large-scale social restrictions.